Tra Esino e San Vicino : architettura religiosa nelle Marche Centrali (secoli xi-xiii) - Cerioni, Cristiano, (Access archaeology., 2021)
This study offers a completely new interpretation of the religious architecture which, between the Romanesque and Gothic periods, established itself in the centre of the Italian Marche region, in an area known as the Valle di S. Clemente.